2011
DOI: 10.1177/0192513x11430820
|View full text |Cite
|
Sign up to set email alerts
|

“The Kids Still Come First”

Abstract: This qualitative study examined the nature of partnerships among 28 rural low-income mothers who experienced partnership transitions across three waves of annual interviews. Guided by lens of uncertainty and boundary ambiguity theory, the authors specifically explored (a) how low-income mothers in rural communities experience partnership transitions over time and (b) how rural, low-income mothers create stability for themselves and their children in the midst of partnership transitions. The narratives of rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…Moreover, the analysis revealed aspects of uncertainty and dependency. The strategies used stand in close connection to a notion of singleparent families as an instable and uncertain form of living together, as described in the lens of uncertainty approach (Burton & Tucker, 2009;Sano, Manoogian, & Ontai, 2012). Uncertainty ascribed to single-parent families derives from a stated lack in complementarity, based on the powerful symbolic meaning of partnerships (Hertz, 2006;Ketokivi, 2012;Nelson, 2006;Sano et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the analysis revealed aspects of uncertainty and dependency. The strategies used stand in close connection to a notion of singleparent families as an instable and uncertain form of living together, as described in the lens of uncertainty approach (Burton & Tucker, 2009;Sano, Manoogian, & Ontai, 2012). Uncertainty ascribed to single-parent families derives from a stated lack in complementarity, based on the powerful symbolic meaning of partnerships (Hertz, 2006;Ketokivi, 2012;Nelson, 2006;Sano et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The strategies used stand in close connection to a notion of singleparent families as an instable and uncertain form of living together, as described in the lens of uncertainty approach (Burton & Tucker, 2009;Sano, Manoogian, & Ontai, 2012). Uncertainty ascribed to single-parent families derives from a stated lack in complementarity, based on the powerful symbolic meaning of partnerships (Hertz, 2006;Ketokivi, 2012;Nelson, 2006;Sano et al, 2012). The concepts of partnership displayed in the present data promote notions of female dependency on a male partner who would represent a source of stability, which implies similarities with Sarkisian's (2006) concept of an ideological father presence in the framework of boundary ambiguity and Nelson's (2006) finding that single mothers reserve a space for a partner's involvement even if there is no specific male partner to take up this role.…”
Section: Discussionmentioning
confidence: 99%
“…These transcripts were not examined because research shows differences among custodial grandparents and other caregivers (Yancura, 2018). Contributions and comparisons between partnered and unpartnered caregivers were also not examined in this study because previous studies in similar samples have demonstrated that many low-income mothers in rural areas experience serial domestic partnerships (Sano, Manoogian, & Ontai, 2012). Finally, we focused on how the rural context may shape grandparent contributions, but we did not consider other key contextual influences such as culture, race/ethnicity, and stigma (Burton et al, 2013).…”
Section: Limitations Of Studymentioning
confidence: 99%
“…Parents attempt to balance the vertical and horizontal elements of their relationships with their children in order to accommodate companionship and mutual enjoyment in these relationships (Nixon, Greene, & Hogan, 2012). Both children and mothers are concerned with maintaining a close and cohesive relationship with one another; mothers attempt to take the mother–child relationship and children’s needs into account when forming and dissolving romantic relationships (Sano, Manoogian, & Ontai, 2012; Weaver & Coleman, 2010). Thus, in the context of family instability, children may hold considerable power within the family unit.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…From this research, it is clear that family instability creates stress and tends to be negative for mother and child outcomes, but less known about relationship development and family dynamics following the dissolution of mothers’ romantic relationships. The few qualitative studies on family transitions have been largely based on interviews with one member of the household (Hogan et al, 2003; Sano et al, 2012) and do not address how experiences of family instability shape the context of further relationship development.…”
Section: The Present Studymentioning
confidence: 99%